Margaret Archer (1943-2023) on Critical Realism and Morphogenesis: Linking Critical Realist Research Models from East and West - Adam-Bagley, Chris; Abubaker, Mahmoud (University of Darussalam Gontor Press, 2023)
Critical Realism (CR) is a philosophical approach to social science research, social action, and social change activism. It provides a framework for social scientists whose value commitments leads them to view the construction of social phenomenon in critical ways, which identify the often hidden oppressive elements in social structures. This understanding of a ‘new’ reality underlies the advocacy of change strategies, and the initiation of dialogue between members of disadvantaged and oppressed groups through the process of ‘morphogenesis’ This model of dialogues enabling change and the ‘unmasking of alienation’ stem from the work of Roy Bhaskar, and has been developed by Margaret Archer and other European scholars. An important feature of CR has been the application by the emergence of shared understanding, by social scientists from different value traditions (e.g. Christianity, Secular Humanism, and Islam). The JOCRISE in taking CR understandings of oppressive social forces into new fields, and with fresh CR models, is welcomed. In appraising the new model from JOCRISE, we offer both Cartesian dualism, and Popper’s World 3 model as elements of a new, dynamic focus on social change advocacy.